VISUAL BIOFEEDBACK IN PHYSIOTHERAPY - Claudia França Dias Batista, Ana; Soares, Gilson; Eduardo Cesar Vieira, Carlos; Armbrust, Danilo; Sérgio Vinhoti, Danilo (Health and Society, 2024)
The Biofeedback is a cognitive treatment which the patient learns and learns to selectively change the neurologic processes with the help of a external monitor. The vision is one of the biofeedback features that helps the patient to get feedback on his performance thus enabling the improvement and voluntarily control. For this to happen there are resources from the most affordable to the highest technology that allows this treatment in conjunction with therapy physical offering to the patient an immediate awareness of his locomotor apparatus, where it is processed in the brain, turning as perception of their body in the space. In 13 articles addressing studied from visual biofeedback with mirror, virtual games, urodynamic and balance platform in patients with neurological injuries and even in healthy subjects, showed satisfactory results well when combined with conventional. This demonstrates that the visual biofeedback is an important resource to be used as a therapeutic tool in physical therapy